Ensino coletivo de piano na escola de música do estado do Maranhão: um relato de experiência - BENEVENUTO, Helen Regina (2020)
In this study, we demonstrate the applicability of collective teaching modality in piano classes of the Music School of the State of Maranhão (EMEM). The main objective of the study was to confirm if this teaching modality meets the needs of students in the initial grades of the EMEM Piano course, more precisely in the first and second periods of the Fundamental Piano course, both for Children and Adults, and if the students participating in this type of teaching would be able to follow the contents of the third period of the course in question. Since it is known that collective teaching of musical instrument has specificities for the student's learning, especially regarding the nexus of social coexistence that provides an interpersonal relationship, it leads us to the idea that such relationship can be beneficial for EMEM students. The motivation for this study arose from the observation of an increasing demand for the piano course, of the small number of teachers working at the school to meet this demand and the existing discrepancy between the number of students entering the Fundamental Piano course and enrollment number in the Technical Piano course of the same Educational Institution. This research is based on the Cooperation System of Johnson, Johnson and Holubec and on the theory of the Zone of Proximal Development of Vygotsky combined with the studies of Robert Pace, Maria de Lourdes Junqueira, Isabel Montandon, and Daniel Lemos Cerqueira, among others. The conclusions reported here resulted from the research conducted during the classes taught at EMEM by the researcher throughout the year 2019. The students were divided into 4 groups, 2 of which consisted of children 8 to13 years of age, and the other 2 groups consisted of teenagers and adults aged between 14 and 58 years old, with about 8 students per class, who had 1-hour long classes once a week, in a room equipped with 9 electronic keyboards. It is expected that this study will contribute for this Institution to offer Piano classes to a larger number of people and, in the future, to aid other Music Teaching Institutions in the adoption of this teaching modality.